Rubrik Moerangkalih dalam Surat Kabar Sipatahoenan sebagai Sarana Edukasi pada Tahun 1935 - Lulu Liani; Asep Ahmad Hidayat (Historia Madania: Jurnal Ilmu Sejarah, 2020)
The development of the press cannot be separated from the emergence of the idealism of the nation's struggle to achieve independence.  One effort to achieve this is by publishing appropriate readings for the nation's successors.  This was done by the Pagoejoeban Pasoendan organization which published a special rubric named moerangkalih in the Sipatahoenan newspaper.  This study aims to determine the history of the establishment of the Sipatahoenan newspaper in 1922-1935 and find out the educational discourse in the rubric of Moerangkalih Sipatahoenan newspaper in 1935. The method used is a historical research method with four stages namely heuristics, criticism, interpretation and historiography.  The results of this study Sipatahoenan was  from the results of the Pagoejoeban Pasoendan conference on 25-26 December 1922 to be published under the leadership of Ahmad Atmaja Pagoejoeban Pasoendan, Tasikmalaya Branch.  On April 29, 1931 Sipatahoenan was transferred to the central board so that a moerangkalih rubric was published which contained appropriate reading for children at that time. Educational elements that can be found include educating readers to better appreciate life, the way to achieve the glory of life, as well as stories that have moral values in it such as how bad deeds someone does will return to him and the consequences of lazy deeds done continuously and repeatedly. Keyword: Newspaper, press, education means